Changes in platelet function independent of pharmacotherapy following coronary intervention in non-ST-elevation myocardial infarction patients. Issue 1 (November 2015) - Freeman, Phillip M.; Moschonas, Konstantinos E.; Hinz, Christine; O'Donnell, Valerie B.; Kinnaird, Tim D.; James, Philip E.; Anderson, Richard A.
Abstract: Background: High on treatment platelet reactivity (HTPR) is common in patients receiving clopidogrel following an acute coronary syndrome (ACS); it's also associated with increased morbidity and mortality. More potent and predictable antiplatelet drugs have addressed this issue at the expense of increased bleeding. Identification of HTPR and the targeted use of more potent antiplatelet drugs has, so far, broadly failed. We investigate this approach in terms of the timing of platelet function testing and how this can impact on the ability of these bedside tests to predict HTPR around the time of coronary intervention. Methods: High risk ACS patients treated with 5 days of clopidogrel had platelet function assessed using the multiple electrode aggregometry system (MEA) pre, post and 24 h following percutaneous coronary intervention (PCI). Simultaneous detailed analysis of platelet status was undertaken with quantification of platelet bound and soluble p-selectin and mass spectrometry quantification of the eicosanoid 12-HETE. Results: As assessed by MEA 40.5% of patients had HTPR pre-PCI; mean aggregation units (AU) in response to ADP were 499.1 ± 46.3 pre-PCI, 407.6 ± 37.7 post-PCI and 269.1 ± 24.6 AU 24 h post-PCI (pre to post PCI p > 0.05, pre to 24 h post-PCI p = 0.0002). This highly significant drop in platelet reactivity was contrasted with on-going expression of platelet bound p-selectin, increased soluble p-selectin and rising 12-HETE concentrations. Conclusions: This study outlines significant changes in ex-vivo platelet aggregation that occur within 24 h of PCI in high risk NSTEMI patients using bedside PFT. Whilst there were no changes in antiplatelet therapy during the study period its clear that timing is crucial when assessing high on treatment residual platelet activity. Highlights: NSTEMI patients treated with chronic clopidogrel (at least 5 days) with no changes to pharmacotherapy. Predictable & large reduction in ADP aggregation 24 h post-PCI using bedside platelet function test (PFT). 12-HETE, soluble and platelet bound p-selectin elevated at 24 h post-PCI. Low ex-vivo ADP signal likely indicates dysfunctional "spent" platelets and suggests PFT should not be used at 24 h post-PCI to inform changes in therapy. Majority of negative tailored therapy trials use post-PCI testing in protocols.